Smart Wound Hydration Monitoring Using Biosensors and Fuzzy Inference System - Sattar, Hina; Bajwa, Imran Sarwar; ul Amin, Riaz; Muhammad, Jan; Mushtaq, Muhammad Faheem; Kazmi, Rafaqut; Akram, Muhammad; Ashraf, Muhammad; Shafi, Umar (Wireless Communications and Mobile Computing, 2019)
Skin wounds either minor or chronic may heal up with different time durations. But, this time duration of healing could not be easily predicted as healing is affected by different factors, e.g., age, nutrition, medication, and surroundings. Despite these factors, wound characteristic also plays a role in the healing process. Wound characteristics include wound size, wound type, internal and external wound environment, body temperature, body oxygenation, wound hydration, and infection. Therefore, monitoring of wound healing also required careful consideration of wound characteristics. Although the healthcare domain contains many applications for detection and monitoring of diseases, the wound care domain requires efficient techniques and sensing systems for the identification of wound biomarkers such as temperature, blood pressure, oxygen, and infection status of wound using biosensors. In the current research, we provide a wound care solution based on a biosensor-based sensing system to measure basic biomarkers, considered as major wound characteristics, i.e., body temperature and body oxygenation, and design a fuzzy inference system to predict their effect on wound hydration, which ultimately recommends necessary actions to boost healing.